Beyond the UN Global Compact : institutions and regulations - Leonard, Liam; Gonzalez-Perez, Maria-Alejandra (Advances in sustainability and environmental justice ;, 2015)
This book offers African, Asian, Latin American, European, and North American perspectives on institutions and regulations promoting sustainable economic growth in the post-2015 development agenda in areas such as environment, labour, risk management, corporate social responsibility, corporate governance, and innovation. The chapters address sustainability issues at the firm, national, regional and international levels from a multidisciplinary perspective. The chapters of this volume address the challenge of enhancing economic competitiveness of the supply side economies while pushing a sustainable development agenda. This work addresses the existing inequalities, environmental degradation, and economic/financial instability under current dynamics of international and domestic power relations in order to meet the set objectives for the post-2015 era. This volume advances the perspectives on the non-compulsory alternative to markets regulations, the United Nations Global Compact, explored in the previous volume 'The UN Global Compact: Fair Competition and Environmental and Labour Justice in International Markets' vol. 16.